Just conservation: What is it and should we pursue it? - Vucetich, JA; Burnham, D; Macdonald, EA; Bruskotter, JT; Marchini, S; Zimmermann, A; Macdonald, DW (Elsevier, 2018)
Efforts to realize conservation are often met with stakeholders contending that particular conservation actions are unfair for conflicting with their basic interests. A useful lens through which to view such conflict is social justice, which may be considered the fair treatment of others judged according three principles: equality, need, and desert (noun form of deserve). We formally demonstrate that (i) the subject of social justice (others) includes many non-human elements of nature and (ii) realizing conservation that is also socially just requires being guided by a non-anthropocentrism principle, whereby no human should infringe on the well-being of others any more than is necessary for a healthy, meaningful life. The concept, “healthy, meaningful life” is less vague and subjective than might be presupposed. That concept is for example subject to considerable objective reasoning through social and behavioral sciences. We indicate how realizing socially-just conservation requires another guiding, safeguard principle: If a significant and genuine conservation interest calls for restricting a human interest, that restriction should occur except when doing so would result in injustice. When the restriction would be unjust every effort should be made by all involved parties to mitigate the restriction to the point of no longer being unjust. This principle covers concerns often raised when conservation is opposed – e.g., financial costs, loss of cultural tradition. We explain how these two principles are neglected or excluded by many methods for resolving conservation conflicts and collaborative governance of natural resources.